IMPLEMENTASI MANAJEMEN MASJID AGUNG AS-SALAM KOTA LUBUKLINGGAU - Dedi Kurniawan; Depi Putri; Sumraini Sumraini (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2021)
This study aims to determine the implementation of the management of the Great Mosque of As-Salam, Pasar Permiri Village, Lubuklinggau Barat II District, Lubuklinggau City, along with the supporting and inhibiting factors. The method used is descriptive qualitative method, using data collection techniques in the form of observation, interviews, and documentation. The results obtained in the form of: Management of the Great Mosque of As-Salam Lubuklinggau has good management and structure. In terms of planning, organizing, directing and evaluating the implementation has been good and is supported by all mosque administrators, the Lubuklinggau City Government and the community. The Great Mosque of As-Salam is more likely to use a formal system, namely the management holds annual, monthly and weekly meetings, this cannot be separated from forming a work program that will be carried out for one period. The supporters of the As-Salam Great Mosque are the full support of the Lubuklinggau City Government and the facilities of the As-Salam Great Mosque. While the obstacles that hinder management towards a better direction are the constraints of the community, the lack of awareness to maintain the existing facilities at the Great Mosque of As-Salam, ack of interest in praying in congregation in mosques, lack of public awareness of participating in giving and giving alms together with the Great Mosque of As-Salam to help people in need, lack of human resources (Human Resources) for mosque administrators in IT ( Information Technology) especially web sites, and members who lack a work ethic, are responsible for trust in their work. Penelitian ini bertujuan untuk mengetahui Implementasi Manajemen Masjid Agung As-Salam Kelurahan Pasar Permiri Kecamatan Lubuklinggau Barat II Kota Lubuklinggau, beserta faktor Pendukung dan Penghambatnya. Adapun metode yang digunakan adalah metode deskriptif kualitatif, dengan menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian yang di peroleh berupa : Manajemen Masjid Agung As-Salam Lubuklinggau memiliki manajemen dan struktur yang sudah bagus. Dari segi perencanaan, pengorganisasian, Pengarahan dan evaluasi yang dijalankan sudah baik dan di dukung oleh semua pengurus Masjid, Pemerintah Kota Lubuklinggau dan masyarakat. Masjid Agung As-Salam lebih cenderung menggunakan sistem formal yaitu pengurus mengadakan rapat tahunan, bulanan dan rapat mingguan, hal ini tidak terlepas dari membentuk program kerja yang akan dilaksanakan selama satu periode. Adapun Pendukung Masjid Agung As-Salam ialah adanya dukungan penuh dari Pemerintah Kota Lubuklinggau dan fasilitas-fasilitas Masjid Agung As-Salam. Sedangkan hambatan yang menghalangi manajemen kearah yang lebih baik ialah kendala dari Masyarakat tidak adanya kesadaran untuk menjaga fasilitas yang ada di Masjid Agung As-Salam, kurang memiliki minat untuk shalat berjama’ah di masjid, kurangnya kepedulian masyarakat ikut serta dalam berinfaq dan sedekah bersama-sama Masjid Agung As-Salam untuk membantu masyarakat yang membutuhkan, Kurangnya SDM (Sumber Daya Manusia) tenaga ahli pada pengurus Masjid di bidang TI (Tehnologi Informatika) khususnya webstite, Serta anggota kurang memiliki etos kerja, bertanggung jawab terhadap amanah dalam bekerja.